1969
DOI: 10.1136/pgmj.45.528.648
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute myocardial infarction treated with hyperbaric oxygen. Report on forty patients

Abstract: SummaryForty patients, aged , who had had an acute myocardial infarct in the preceding 24 hr, and who were seriously ill, were treated in a hyperbaric oxygen bed at 2 atm (atmospheres) absolute for sessions of 2 hr in and 1 hr out for an average period of 4 days.There were thirty-seven survivors after the treatment, giving an immediate mortality of 7 5 %, but three ofthose died later before leaving hospital, giving a total mortality of 15% in seriously ill patients.Pain and dyspnoea were usually improved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In animal stud-ies, HBO also reduces the ischemic effects of coronary artery occlusion [7][8][9][10]. However, prior human trials detected little substantial benefit from HBO without concomitant thrombolysis [11][12][13][14]. The only controlled trial, done in the prethrombolytic era, revealed a trend but no statistically significant mortality benefit when standard methods of analysis were used [15].…”
Section: Introductionmentioning
confidence: 99%
“…In animal stud-ies, HBO also reduces the ischemic effects of coronary artery occlusion [7][8][9][10]. However, prior human trials detected little substantial benefit from HBO without concomitant thrombolysis [11][12][13][14]. The only controlled trial, done in the prethrombolytic era, revealed a trend but no statistically significant mortality benefit when standard methods of analysis were used [15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they found that the mortality rate for high-risk groups may have been reduced by 02 to about half. Ashfield and Gavey (1969) came to a similar conclusion using 40 patients with acute myocardial infarction. They found that 02 was beneficial in the more severe cases : the worse the pain the more 02 seemed to help.…”
Section: Discussionmentioning
confidence: 54%
“…Patients with acute myocardial infarction, which was our main interest, are described in more detail in the next paper (Ashfield & Gavey, 1969).…”
Section: Acute Myocardial Infarction (Forty Cases)mentioning
confidence: 99%